(untitled) (UNED Research Journal, 2019)
Four sampling trips (2016 and 2017) in Río Grande de San Ramón (Tárcoles River Basin, 1 060masl) produced nine species, three of them for the first time for this altitude or basin. Previously, Alfaro cultratus (N=95) was reported only up to 300masl at the Caribbean slope and in the Tempisque River basin; Amatitlania siquia (N=4) only under 540masl for the Tárcoles river basin; and Amatitlania septemfasciata (N=22) from the Atlantic slope and below 600 masl.